Perlindungan Hukum Bagi Masyarakat Indonesia Yang Menjadi Korban Perdagangan Manusia di Luar Negeri - Putri, Amelia; Prasetyo, Handoyo (Media Hukum Indonesia (MHI), 2024)
Indonesia is a country of law, all actions in Indonesia are regulated and bound by law. Human trafficking takes the form of an organized criminal act which is carried out using both conventional methods such as persuasion from labor recruiters at the village level to modern methods. The practice of human trafficking has become a crime that takes many victims from the public, especially people who have low incomes and low levels of education. In Indonesia, human trafficking takes the form of a crime that has the aim of sexual exploitation, domestic servants, housemaids, migrant workers, child labor, and arranged marriages. The end result of these crimes is that the victims are forced to work under poor working conditions and for inadequate wages. Cases of criminal acts have attracted public attention recently, this is also what attracted the attention of the writer to explore further the case of Indonesian citizens suspected of being victims of criminal acts of human trafficking in Myanmar. The research method used in this research is qualitative. To obtain the data needed in this research, the author conducted library research. Literary research is carried out to obtain secondary data by studying regulations, literature, including general references such as books, journals and so on. Factors that trigger the crime of human trafficking in Indonesia include poverty, education, lack of access to information, early marriage and divorce, difficulty finding work and so on.